Analisis Determinan Tingkat Kemiskinan Perempuan Lansia Provinsi DI Yogyakarta Tahun 2020 - Cholily, Vebrina Hania (Jurnal Indonesia Sosial Sains, 2022)
In 2020, Indonesia experienced an increase in the number of poor people by 10.19% with a total poor population of 26.42 million people. By definition, poverty is the inability from an economic point of view to meet the basic needs of food and non-food as measured from the expenditure side. The elderly tend to have a high poverty rate and elderly women have a greater potential to be in poor conditions with the percentage of poor elderly women being 9.96%. DI Yogyakarta is a province with an elderly poverty rate and the highest number of elderly population in Indonesia with an elderly percentage of 14.71% in 2020. Therefore, a solution is needed to minimize the number of poor elderly women in the DI Yoyakarta Province by knowing the factors that cause poverty in Yogyakarta elderly female level.This study was proposed with the aim of knowing the factors that influence the poverty of elderly women in the Province of DI Yogyakarta. The type of data used is primary data obtained from 799 samples of elderly women in DI Yogyakarta Province and secondary data as supporting data in this study. The analytical method used in this study is binary logistic regression. The variables in this study include: length of schooling, ability to access information and communication technology, labor participation, number of hours worked, marital status, health complaints and outpatient history.The results showed that the variables of school years, ability to access information and communication technology, labor participation, number of hours worked, health complaints and outpatient history had a significant effect on the poverty of elderly women in DI Yogyakarta Province. While the variable that does not significantly affect the poverty of elderly women in the Province of DI Yogyakarta is marital status, so that this variable does not have the opportunity to affect the poverty of elderly women in the Province of DI Yogyakarta.